The NADPH Oxidase Isoform 1 Contributes to Angiotensin II-Mediated DNA Damage in the Kidney - Anna Zimnol; Nora Spicker; Ronja Balhorn; Katrin Schröder; Nicole Schupp (MDPI AG, 2020)
In higher concentrations, the blood pressure regulating hormone angiotensin II leads to vasoconstriction, hypertension, and oxidative stress by activating NADPH oxidases which are a major enzymatic source of reactive oxygen species (ROS). With the help of knockout animals, the impact of the three predominant NADPH oxidases present in the kidney, i.e., Nox1, Nox2 and Nox4 on angiotensin II-induced oxidative damage was studied. Male wildtype (WT) C57BL/6 mice, Nox1-, Nox2- and Nox4-deficient mice were equipped with osmotic minipumps, delivering either vehicle (PBS) or angiotensin II, for 28 days. Angiotensin II increased blood pressure and urinary albumin levels significantly in all treated mouse strains. In Nox1 knockout mice these increases were significantly lower than in WT, or Nox2 knockout mice. In WT mice, angiotensin II also raised systemic oxidative stress, ROS formation and DNA lesions in the kidney. A local significantly increased ROS production was also found in Nox2 and Nox4 knockout mice but not in Nox1 knockout mice who further had significantly lower systemic oxidative stress and DNA damage than WT animals. Nox2 and Nox4 knockout mice had increased basal DNA damage, concealing possible angiotensin II-induced increases. In conclusion, in the kidney, Nox1 seemed to play a role in angiotensin II-induced DNA damage.